Gendered impacts of greenhouse gas mitigation options for rice cultivation in India - Gartaula, Hom Nath; Sapkota, Tek Bahadur; Khatri-Chhetri, Arun; Prasad, Gokul; Badstue, Lone B. (Springer, 2020)
The nexus of gender-agriculture-emissions reduction is one of the least explored areas related to agriculture and climate change. This nexus plays an important role in the areas where women’s participation in agriculture is high, and the contribution of the agricultural sector to total emission is significant. This study generates evidence on women’s labor contribution in rice cultivation and potential reduction of their labor drudgery, including GHG mitigation co-benefits with the adoption of direct seeding and machine transplanting technologies. Using a large number of plot-level data (11,987 data points) from the rice-growing regions of India, the study shows that changing rice production technology from conventional to direct-seeded rice (DSR) and/or machine-transplanted rice (MTR) offers huge potential to reduce women’s labor in rice planting (745 million labor-days for DSR and 610 million labor-days for MTR) and greenhouse gases (GHG) emission (34 MtCO2e for DSR and 7 MtCO2e for MTR) at the same time. This potential differs from the agro-ecological region, the level of input use, and women’s involvement in rice cultivation. The realization of this gender-responsive GHG mitigation strategy depends on the adoption of these technologies, which rely on several social, economic, and political factors. At the same time, the immense potential for negative implications for some specific groups should not be ignored, but focused on addressing and mitigating those challenges.